2016
DOI: 10.1016/j.bbi.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to an inflammatory challenge enhances neural sensitivity to negative and positive social feedback

Abstract: Inflammation, part of the body’s innate immune response, can lead to “sickness behaviors,” as well as alterations in social and affective experiences. Elevated levels of pro-inflammatory cytokines have been associated with increased neural sensitivity to social rejection and social threat, but also decreased neural sensitivity to rewards. However, recent evidence suggests that inflammation may actually enhance sensitivity to certain social rewards, such as those that signal support and care. Despite a growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 34 publications
9
103
1
Order By: Relevance
“…Results from this study revealed that, in response to negative (vs neutral) feedback, subjects exposed to the inflammatory challenge showed greater activity in the dACC as well as the amygdala, a neural region that responds, in part, to threat (Muscatell et al, 2016). Thus, again, an inflammatory challenge led to increased sensitivity to a negative social experience.…”
Section: Neural Sensitivity To Negative Social Experiencementioning
confidence: 67%
See 3 more Smart Citations
“…Results from this study revealed that, in response to negative (vs neutral) feedback, subjects exposed to the inflammatory challenge showed greater activity in the dACC as well as the amygdala, a neural region that responds, in part, to threat (Muscatell et al, 2016). Thus, again, an inflammatory challenge led to increased sensitivity to a negative social experience.…”
Section: Neural Sensitivity To Negative Social Experiencementioning
confidence: 67%
“…To date, two broad categories of social experience have been found to be altered as a function of inflammation. Specifically, inflammation alters neural sensitivity to negative social stimuli or experiences (eg, social rejection, receiving negative social feedback, and viewing threatening faces; Eisenberger et al, 2009;Inagaki et al, 2012;Muscatell et al, 2016) as well as sensitivity to positive social stimuli or experiences (eg, viewing close others and receiving positive social feedback; Inagaki et al, 2015;Muscatell et al, 2016). A heightened sensitivity to both positive and negative social stimuli may help an individual to more quickly determine which individuals might be supportive and provide help in times of need and which individuals will not and should be avoided.…”
Section: Effects Of Inflammation On Social Behavior In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, typhoid vaccination compared with saline has been shown to affect activity in the substantia nigra, including increased activation during a cognitive Stroop task and decreased activation in response to visual or novel stimuli, which correlated with both psychomotor slowing and increased peripheral blood concentrations of IL-6 (Brydon et al, 2008;Harrison et al, 2015a). Finally, it should be mentioned that neural activation in reward circuitry (ventral striatum and ventromedial PFC (vmPFC)) has also been shown to encode endotoxin-induced increased sensitivity to social rewards, including positive social feedback and increased approach to familiar others (Inagaki et al, 2015;Muscatell et al, 2016).…”
Section: Neuroimaging Of the Da System And Corticostriatal Reward Cirmentioning
confidence: 98%